2004
DOI: 10.1890/03-0513
|View full text |Cite
|
Sign up to set email alerts
|

Yellow-Bellied Marmot Population Dynamics: Demographic Mechanisms of Growth and Decline

Abstract: Abstract. Multiple environmental factors may act synergistically to influence demographic characteristics, and ultimately the dynamics, of biological populations. Using prospective and retrospective analyses of demographic data from a 40-year study of individually marked animals, we investigated the demographic mechanisms of the temporal and spatial dynamics of a yellow-bellied marmot (Marmota flaviventris) population. Prospective elasticity analyses indicated juvenile survival (P j ) would have the largest re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
56
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 48 publications
3
56
2
Order By: Relevance
“…Theory predicts that demographic parameters to which population growth rate is highly sensitive should be less variable than those to which growth rate is less sensitive (Cairns 1992;Gaillard et al 1998Gaillard et al , 2000Pfister 1998). Oli and Armitage (2004) found that asymptotic growth rate of a yellow-bellied marmot population was generally more sensitive to changes in survival parameters than to reproductive parameters. Thus, we expected survival parameters to be less variable over space or time than reproductive parameters.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Theory predicts that demographic parameters to which population growth rate is highly sensitive should be less variable than those to which growth rate is less sensitive (Cairns 1992;Gaillard et al 1998Gaillard et al , 2000Pfister 1998). Oli and Armitage (2004) found that asymptotic growth rate of a yellow-bellied marmot population was generally more sensitive to changes in survival parameters than to reproductive parameters. Thus, we expected survival parameters to be less variable over space or time than reproductive parameters.…”
Section: Introductionmentioning
confidence: 95%
“…Reproduction is an important life history trait that can be particularly sensitive to spatiotemporal variation in the environment (Caswell 2001;Coulson et al 1999Coulson et al , 2000Heppell et al 2000). Because population growth rates are highly sensitive to changes in reproductive parameters in many species (e.g., Oli and Armitage 2004;Oli and Dobson 2003;Saether and Bakke 2000), spatiotemporal variation in these rates can influence the dynamics and persistence of populations. Therefore, a thorough understanding of population dynamics requires a detailed Communicated by John Reeve.…”
Section: Introductionmentioning
confidence: 99%
“…Retrospective perturbation analyses, such as life table response experiments (LTRE), allow scientists to evaluate how variation in specific vital rates contributed to past population dynamics (Caswell 2000, Oli andArmitage 2004) whereas prospective perturbation analyses, such as sensitivity and elasticity analyses, quantitate how equivalent changes in vital rates would affect future population growth. Collectively, these demographic tools can provide critical information about the ecology and life history of a species, prioritize research and conservation actions, and help develop species recovery plans (Crowder et al 1994, Doak et al 1994, Caswell 2001.…”
Section: Introductionmentioning
confidence: 99%
“…After a rather heated debate about the relative roles of exogenous (density-independent, Andrewartha and Birch 1954) versus endogenous (densitydependent, Nicholson 1957) factors influencing population dynamics, there is now broad consensus that both factors are important (Leirs et al 1997;Grenfell et al 1998;Coulson et al 2001Coulson et al , 2004aAars and Ims 2002;Ozgul et al 2004;Oli and Armitage 2004). Whereas density dependence is considered a ubiquitous feature of the dynamics of many populations (May 1973;Fryxell et al 1991;Royama 1992;Forchhammer et al 1998), recent work has emphasised that the interaction between a density-dependent ''skeleton'' and a stochastic ''noise'' component can enhance our understanding of population dynamics (Leirs et al 1997;Cushing 1998;Krüger et al 2002;Coulson et al 2004a).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, a link between individual life histories, population demography and population dynamics might O. Krüger (&) Department of Zoology, University of Cambridge, Downing Street, Cambridge CB2 3EJ, UK e-mail: ok212@cam.ac.uk prove fruitful in generating a deeper understanding of the causes and mechanisms (de Kroon et al 2000;Oli and Armitage 2004), because individual fitness properties are bound to have consequences at population level (Sutherland 1996). Such a link necessitates long-term, individual-based studies, which have recently emerged in comparative abundance (e.g.…”
Section: Introductionmentioning
confidence: 99%